SAFETY CULTURE TO PREVENT INFECTION IN NORMAL BIRTH CARE BY VILLAGE MIDWIVES ATEAST LOMBOK NUSA TENGGARA BARAT - Bartini, Istri (Universitas Ahmad Dahlan, 2015)
Background: Normal birth care is one of midwifeâs competence within the most of risks to both women and midwife. Limited of health facilities and social culture are major problem of midwifery care. In fact, infection cases have been occurring and become a significant cause in maternal death. At East Lombok most of 93,33% birth was provided by midwife. It was a tricky to explain that midwife does not work as well.Aim: to describe safety culture to prevent infection during normal birth care at rural area.Method: qualitative study with focus group discussion and in-depth have done for 8 midwives from 6 sub-district at East Lombok. We selected midwife who have done at least 1 year and have experience in preventing infection during birth care.Result: Midwives struggled to perform the rule of normal birth care with the limited facilities. Cultural sensitivity restricted to use personal protective equipment. To build safety culture in their work, social culture became an obstacles more than support system and policy. Lack of knowledge about safety care on rural area is one of problem they said.Conclusion: Culture sensitivity is something to consider in safety care, although considerable to standard care is essential in midwifery care. Culture safety care concept particularly for prevent infection at remote area are needed to expand in the midwifery curriculum.Â Â